The Impact of Market Knowledge on Adopting the Proactive Strategic Direction of the Economic Institution- A Survey Study From the Point of View of the Managers of the Cement Establishment in Ain El-Kabira Setif- - بن ميهوب أمينة; هباش فارس (Finance and Business Economies Review, 2021)
This study aimed to determine the impact of market knowledge on the proactive strategic direction of the economic institution through the viewpoint of the managers of the cement company in Ain El Kabeira - Setif, based on a hypothetical model that takes into account the nature of the relationship between market knowledge defined by: (customer knowledge, competitor knowledge, Knowing the products, knowing the resource) the proactive strategic direction of the economic institution. The study reached a set of results, the most important of which are: that there is a positive and statistically significant impact of market knowledge on the proactive strategic direction of the economic institution, and the most important recommendations that are based on the procedures and conditions necessary to provide and activate this knowledge in the institution under study were proposed.